A Longitudinal Study of Age-Based Change in Blood Pressure Reactivity and Negative Affect Reactivity to Natural Stressors. Issue 5 (12th June 2022) - Koffer, Rachel E.; Kamarck, Thomas W.
ABSTRACT: Objective: Aging is theoretically accompanied by emotional gains, but physiological self-regulatory losses. Emotional and physiological regulation can be operationalized as the extent of an increase in negative affect and blood pressure upon experiencing a stressor (i.e., reactivity). The direction of age-based changes in negative affect reactivity to stressors is uncertain. In addition, evidence for age-based increases in blood pressure reactivity to stressors is based largely on age-based differences observed in cross-sectional and laboratory-based studies. The present study is the first to examine long-term longitudinal changes in stress-related reactivity for both blood pressure and negative affect in the natural environment. Methods: A total of 375 healthy adults aged 50 to 70 years completed 6 days of hourly ambulatory blood pressure assessment and electronic diary reports of social conflict and task demand and control. Two hundred fifty-five participants repeated 3 days of assessment in a 6-year follow-up. With reactivity operationalized as the change in an outcome in association with momentary social conflict, task strain, or task demand (i.e., a model-derived slope parameter), multilevel models were used to assess aging-based change in blood pressure and negative affect reactivity over the course of the 6-year follow-up. Results: Aging is associated with increased diastolic blood pressure reactivity to social conflict and task demand ( β social_conflict = 0.48, p = .007; β task_demand = 0.19, p = .005), increases in negative affect reactivity to social conflict and task strain ( β social_conflict = 0.10, p < .001; β task_strain = 0.08, p = .016), and increases in systolic blood pressure reactivity to task-based stress ( β task_strain = 1.29, p = .007; β task_demand = 0.23 p = .032). Conclusion: Findings suggest age-based increases in affective and cardiovascular reactivity to natural stressors.